Wilhelm Reich e a bússola do pensamento funcional - Costa, Magali de Moraes Rego (2002)
Wilhelm Reich (*1897-t1957) states the existence of the cosmic orgone energy - OR and its variation in the living organism, bioenergy. The OR' s metabolism implies in the possibility of deterioration into deadly orgone - DOR living and non-living nature. The ORDOR balance expresses the uncertainty of the vital processes, in states of disease or health. The living human being can function in energetic motility. The functional thinking is the human being in energetic motility thinking. It gathers intuition and logics of reasoning. Intuition consists in the coutact with sensoriality. The logic of reasoning of the functional thinking is non-linear; it identifies functions and unites them to the common functioning principle, wich rules and permeates the functioning field. Orgonomic functionalism constitutes a method wich implies in the functional unity of the living. Without crossing over the concepts between the fields, orgone energy, life and thinking, the orgonomic functionalism seeks to think the simplicity of the energetic movement that surpasses complexities. The orgonomic thinking aims at the understanding of the totality and unity of the orgone energy, wich pulsates, just functions and does not establish anything. The human being experiences life according to his orgonotic pulsation. There are no certainties for the human being. The functional thinking's compass can guide him.